Respuesta :
Answer:
Step-by-step explanation:
A tangent vector to the curve of intersection is given by N1 × N2
Where N1 is normal to the graph of
G(x, y, z) = z= x² + y² at the point P(-1,1,2) and
N2 is normal to the level surface
F(x, y, z)=4x² + 3y²+ 7z²= 35 at the point P(-1,1,2).
Now,
G(x, y, z)=x²+y²-z
Then, taking the grad of G will give a vector perpendicular to the paraboloid
∇G = ∂G/∂x •i + ∂G/∂y •j + ∂G/∂z •k
∇G= 2x•i +2y•j -k
At the point (-1,1,2)
N1=(-2,2,2)
Also to get N2
F(x, y, z)=4x² + 3y²+ 7z² - 35
∇F = ∂F/∂x •i + ∂F/∂y •j + ∂F/∂z •k
∇F = 8x•i + 6y•j + 14z•k
At point (-1,1,2)
N2=(-8,6,28)
Computing N1×N2
Note
i×i=j×j=k×k=0
i×j=k, j×i=-k
j×k=i, k×j=-i
k×i=j, i×k=-j
Then,
a×b= (a•i + b•j + c•k) × (x•i + y•j + z•k)
a×b = a•i×(x•i + y•j + z•k) + b•j×(x•i + y•j + z•k) + c•k×(x•i + y•j + z•k)
a×b= (a•i × x•i)+ (a•i × y•j) + (a•i × z•k) + (b•j × x•i) + (b•j × y•j) + (b•j × z•k) + (c•k × x•i) + (c•k × y•j) + (c•k × z•k)
a×b= 0 + ay•k - az•j - bx•k + 0 + bz•i + cx•j - cy•i + 0
a×b= ay•k - az•j - bx•k + bz•i + cx•j -cy•i
Then, rearranging
a×b= (bz - cy)•i+ (cx - az)•j + (ay-bx)•k
Now let assume that
N1=(-2,2,2) a=-2, b=2 and c=2
N2=(-8,6,28) x=-8, y=6 and z=28
N1×N2=(56-12)•i+(-16+56)•j+(-12+16)•k
N1×N2=44i + 40j + 4k
We compute N1 × N2 = (44,40,4) which is tangent to the curve of intersection at the point P.
The equation of the line is given as
x=r + λt
Where r is the point (-1,1,2)
And λ is the direction (44,40,4)
Hence the tangent line is given by
x = 1 + 44t, y = −1 + 40t, z = 2 + 4t.
The required parametric equation is,
[tex]x=-1+62t\\y=1+64t\\z=2+4t[/tex]
Equation of tangent plane:
The formula for the equation of the tangent plane is,
[tex]\left\langle x-x_0,y-y_0,z-z_0 \right\rangle=0[/tex]
The given equation is,
[tex]z = x^2 + y^2[/tex]
And the ellipsoid [tex]4x^2 + 3y^2 + 7z^2 = 35[/tex] at the point [tex](-1, 1, 2)[/tex]
Let, [tex]F= x^2 + y^2-z[/tex] then,
[tex]\nabla F=\left\langle 2x,2y,-1 \right\rangle\\[/tex]
At (-1,1,2) [tex]\nabla F=\left\langle -2,2,-1 \right\rangle\\[/tex]
And [tex]G=4x^2 + 3y^2 + 7z^2 -35[/tex] then,
[tex]\nabla G=\left\langle 8x,6y,14z \right\rangle\\[/tex]
At (-1,1,2) [tex]\nabla G=\left\langle -8,6,28 \right\rangle\\[/tex]
[tex]n=\left| \begin{matrix}\hat{i} & \hat{j} & \hat{k} \\-2 & 2 & -1 \\ -8& 6& 28\end{matrix} \right|\\=\left\langle 62,64,4 \right\rangle[/tex]
Now, applying the above formula we get,
[tex]\left\langle62,64,4 \right\rangle \left\langle x+1,y-1,z-2\right\rangle=0\\62(x+1)+64(y-1)+4(z-2)=0\\31x+32y+2z-5=0[/tex]
The parametric equations are,
[tex]x=-1+62t\\y=1+64t\\z=2+4t[/tex]
Learn more about the topic equation of the tangent plane:
https://brainly.com/question/26153770